ChemInform Abstract: Construction of Dispirocyclohexanes via Amine‐Catalyzed [2 + 2 + 2] Annulations of Morita—Baylis—Hillman Acetates with Exocyclic Alkenes. Issue 22 (15th May 2015) - Chen, Rongshun; Xu, Silong; Fan, Xia; Li, Hanyuan; Tang, Yuhai; He, Zhengjie
Abstract: The presented method offers a novel and efficient one‐step procedure for the construction of complex architectures bearing a dispirocyclohexane motif.